Serum ALT activity and its isoenzymes as potential biomarkers for diagnosis of Sarcopenia in older adults: a retrospective, cross-sectional study - Jiangping Zeng; Nannan Li; Jiaying Ge; Huihui Ma; Siqi Sun; Yujie Jing; Chunhua Qian; Ran Cui; Shen Qu; Hui Sheng (BMC Geriatrics)
Abstract Background Alanine aminotransferase (ALT) is an enzyme crucial for energy and protein metabolism in muscle cells. Despite this, its association with sarcopenia remains inadequately explored. This study aims to investigate the correlation between serum levels of ALT-related indicators (ALT activity, ALT1, ALT2, and ALT1/ALT2 ratio) and sarcopenia measures, as well as to develop a diagnostic model for sarcopenia in older individuals. Methods This retrospective study assessed 653 older adults (aged ≥ 55 years), 109 of whom were studied for the association of ALT1, ALT2, and ALT1/ALT2 ratio with sarcopenia measures. Muscle mass was measured by dual energy X-ray absorptiometry. Hand grip strength (HGS) was measured with a digital dynamometer, and physical performance was assessed through the 6-meter gait speed and the five-times sit-to-stand test (FTSST). Binary logistic regression analysis was used to evaluate associations between ALT-related indicators (ALT activity and ALT1/ALT2 ratio) and sarcopenia. The diagnostic model was developed using binary logistic regression with backward selection, and the diagnostic performance of the model was evaluated by the receiver operator characteristic curve (ROC) curve. Results Older adults with sarcopenia exhibited a lower serum ALT activity and a higher ALT1/ALT2 ratio compared to those without sarcopenia. ALT activity tertiles, but not ALT1 or ALT2 tertiles alone, correlated with HGS, gait speed, FTSST, and appendicular skeletal muscle mass index (ASMI), serving as independent protective factors for low HGS, low physical performance, low ASMI, and sarcopenia. Tertiles of the ALT1/ALT2 ratio were significantly associated with HGS and FTSST, and were proved independent risk factors for low physical performance and sarcopenia by binary logistic regression analysis. An optimal Model A (based on ALT activity) was established for sarcopenia to develop a new Logit_P1 (p < 0.001). Similarly, an optimal Model B (based on ALT1/ALT2 ratio tertiles) was established for sarcopenia to develop a new Logit_P2 (p < 0.001). According to the ROC curve analysis for discriminating sarcopenia, the performance of Logit_P2 (area under the curve = 0.830) seemed better than that of Logit_P1 (area under the curve = 0.789), although the difference was not statistically significant (p = 0.214). Conclusions In older adults, a low serum ALT activity level was an independent risk factor for low ASMI, HGS, physical performance, and sarcopenia. The serum ALT1/ALT2 ratio emerged as an independent risk factor for low physical performance and sarcopenia. The new indices, Logit_P1 and Logit_P2, demonstrated diagnostic value for sarcopenia.